FENOMENA LINUX, SUATU TEROBOSAN NETWORK ORGANIZATION DALAM ERA PEMASARAN RELASIONAL - Dudi Anandya (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2003)
Linux is an operating system that it's presence offer many